FINANCIAL DISTRESS DETERMINANTS DURING COVID-19 PANDEMIC: EVIDENCE FROM NON-FINANCIAL FIRMS IN INDONESIA - Rifka Indi; Yunieta Anny Nainggolan (Fakultas Ekonomi Universitas IBA, 2023)
The COVID-19 pandemic has caused massive bankruptcy for companies in the world. Companies should aware variables signalling aggravated financial distress to give an early-warning system. The objective of this study is to investigate the influence of business strategy, investment policy, and corporate governance to the financial distress. We collect data from the non-financial sector companies in Indonesia. We use logistic regression to test the hypothesis. This research finds that business strategy and female board negatively significant at distress probability, whereas investment policy and board meeting positively significant at the likelihood of financial distress. Further researchers can broaden their scope of investigation to the financial industry and other developing countries.